Manajemen Kinerja dalam Meningkatkan Kualitas Pelayanan - Dhea Rafifah; Nurseri Hasnah Nasution; Emi Puspita Dewi (Social Science and Contemporary Issues Journal, 2023)
This study aimed to determine the performance of employees at KUA in the Alang-Width sub-district of Palembang City, to determine the quality of service at the Alang-Width KUA in Palembang City, and to determine performance management in improving service quality at the Alang-Width KUA in Palembang City. The type of research used is qualitative research. Data collection techniques include observation, interviews, and documentation. The results of the first study, performance, are significant. Good performance will result in effective and maximum service because employees have a high level of education, creativity, initiative, work experience, and ability. A good work ethic can increase employees' abilities in their respective fields. Second, reliability: service providers also understand what the community wants so that no community complains about unclear and lengthy services. Responsiveness: trying to provide the best service in other fields. Even the KUA itself was once exemplary. Assurance: has guaranteed the best possible service. Empathy: the kindness and friendliness of the community, as well as mutual respect and gratitude, is also one of the characteristics of exemplary public service. Tangibles: view of service providers and facilities at KUA, Alang-Width sub-district, Palembang City. Third, performance planning: by determining a planning system to obtain land to construct religious affairs office facilities as a whole and complete. Performance implementation: excellent service is to provide the best possible service to customers so that customers feel satisfied.